PRACTICAL METHODS OF TEACHING NATURAL SCIENCE AND THEIR IMPORTANCE IN STUDYING NATURE (Multidisciplinary Journal of Science and Technology, 2025)
This article highlights the importance of using practical methods in teaching natural science. Through practical lessons, experiments, observations, and excursions, students develop skills to study natural phenomena directly, analyze them, and relate them to real life. Furthermore, these methods play an important role in developing students’ ecological culture and enhancing their sense of love and responsibility toward nature.